Issues in the Unification of Financial Sector Supervision - Abrams, Richard (IMF Working Papers; Working Paper, 2000)
The paper considers the generic arguments for and against the creation of a unified regulatory agency, covering each of the main types of financial institutions (banks, insurers and securities firms). The strongest arguments for unification are the enhanced oversight of financial conglomerates and the economies of scale they can potentially deliver. However, there are also a number of potentially serious disadvantages to unification, especially the risk that the change process will be mismanaged and will result in a reduction in regulatory capacity. The issue requires careful deliberation and ultimately depends on a matrix of factors which vary in importance from country to country.